Structural exploration of antibacterial activity and hemolytic profiles of non-natural analogs of the antimicrobial peptide mastoparan mp-8 (2013)
In this work the relevance of a systematic replacement of peptide-bonds on the Mastoparan MP-8 antimicrobial peptide to afford 27 new pseudopeptide analogues is reported. Results allowed to determine that pseudopeptides ψ-38617 (INLKALAALAKd-[CH2NH]-RLL), ψ-38629(INLKAd-[CH2NH]-LAALAKRLL) and ψ-38630 (INLK-[CH2NH]-ALAALAKRLL), showed an enhanced anti gam-negative bacterial properties, regarding the native Mastoparan MP-8 peptide, but maintaining a comparable activity against gram-positive bacteria. In addition, specific performed modifications on MP-8 sequence led three new molecules that completely abolished the hemolytic activity of the parent MP-8 peptide. All obtained molecules possess a high stability profile when tested against a severe proteolytic attack.